Advances and Applications in Deep Learning 2020
DOI: 10.5772/intechopen.93289
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Enabled Nanophotonics

Abstract: Deep learning has become a vital approach to solving a big-data-driven problem. It has found tremendous applications in computer vision and natural language processing. More recently, deep learning has been widely used in optimising the performance of nanophotonic devices, where the conventional computational approach may require much computation time and significant computation source. In this chapter, we briefly review the recent progress of deep learning in nanophotonics. We overview the applications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Several review articles have been published recently, which categorize in great detail the latest developments of deep learning applications in photonics and nano-optics. For an exhaustive overview we therefore invite the reader to consult these articles [29][30][31][32][33]. Also a few thematically more distantly related review articles have been published recently, which we want to indicate to the interested reader.…”
Section: This Work and Its Positioning With Respect To Other Reviewsmentioning
confidence: 99%
“…Several review articles have been published recently, which categorize in great detail the latest developments of deep learning applications in photonics and nano-optics. For an exhaustive overview we therefore invite the reader to consult these articles [29][30][31][32][33]. Also a few thematically more distantly related review articles have been published recently, which we want to indicate to the interested reader.…”
Section: This Work and Its Positioning With Respect To Other Reviewsmentioning
confidence: 99%
“…Due to the decrease of the total volume size of the Si nanoresonators after the air hole is introduced, one sees that the resonant positions for the transmission valley and peak have shifted together towards the shorter wavelength direction as compared to Figure 1. For an inverse design of the large number of filters with various central wavelengths, it is worth noting that the machine learning approach can be applied, which can introduce the remarkable design flexibility, that can exceed performance of the conventional optimisation methods for such types of the inverse design problems in nanophotonics [53][54][55][56] . Circular displacement currents are excited inside the Si nanodisk, as depicted by the electric near-field images shown in Figure 3(b-d), indicating the excitation of the longitudinal MD resonance.…”
Section: Design Of Metasurfacesmentioning
confidence: 99%
“…A DL-assisted inverse design technique was reported for PCM-based tunable metasurfaces. 54 All of these reports, however, consider a single material throughout the study. Kiarashinejad et al 55 reported the inverse design of 1D metagratings using GST to achieve reconfigurable reflectivity.…”
Section: Introductionmentioning
confidence: 99%